Relationship between Reproductive Health Knowledge and Personal Hygiene Behavior During Menstruation in Adolescents - Ferdiana Ferdiana; Riris Idiawati Riris Idiawati (Minsight: Midwifery Insight and Innovation Journal, 2026)
This study aimed to analyze the relationship between reproductive health knowledge and personal hygiene behavior during menstruation among adolescents. Adequate knowledge of reproductive health is considered an important factor influencing menstrual hygiene practices, which play a crucial role in preventing reproductive tract infections. This research employed a quantitative cross-sectional design involving adolescent female students selected through a simple random sampling technique. Data were collected using a structured questionnaire measuring levels of reproductive health knowledge and menstrual hygiene behaviors. The data were analyzed using the chi-square test to determine the relationship between the two variables. The results showed that most respondents had a moderate level of reproductive health knowledge and adequate personal hygiene behavior during menstruation. Statistical analysis indicated a significant relationship between reproductive health knowledge and personal hygiene behavior (p < 0.05), suggesting that better knowledge is associated with improved hygiene practices. These findings highlight the importance of reproductive health education in schools to enhance adolescents’ awareness and behavior regarding menstrual hygiene. The study implies that strengthening health education programs can contribute to better menstrual hygiene management and reduce the risk of reproductive health problems among adolescents.